A novel strategy for active compound efficacy status identification in multi-tropism Chinese herbal medicine (Scutellaria baicalensis Georgi) based on multi-indexes spectrum-effect gray correlation analysis. (10th January 2023) - Deng, Xin; Lei, Hong-Yuan; Ren, Yong-Shen; Ai, Jiao; Li, Yan-Qiu; Liang, Shuai; Chen, Lin-Lin; Liao, Mao-Chuan
Abstract: Ethnopharmacological relevance: Bioactive substance identification is always the focal point and the main challenge in Chinese herbal medicine (CHM). Most CHM present multiple efficacies and multiple tropisms, which has improved the application accuracy of CHM, and is worthy of further study. In this article, the concept of " multi-tropism efficacy of CHM" has been proposed for the first time. In addition, it is hypothesized that the different components in CHM can be classified based on their efficacy status. Aim of the study: The spectrum-effect relationship between the fingerprint and efficacy was established to identify the efficacy status of components. This provided a practical, efficient and accurate way to identify the bioactive substances from a complex CHM system. Materials and methods: The network pharmacology approach was applied to preliminarily analyze the potential antibacterial compounds and mechanisms of HQ. Furthermore, its chemical fingerprint was established and the characteristic peaks were identified by LC-MS/MS. The antibacterial and anti-inflammatory bioactivities of HQ were determined to evaluate its pharmacological effect of heat-clearing and detoxification, and its anticoagulation activity was determined to evaluate its heat-clearing and tocolysis effects. The spectrum-effect relationships were assessed by gray correlation analysis to discriminate the status of active components in HQ with different efficacies. Results: Network pharmacology analysis revealed apigenin, wogonin, baicalein, acacetin, β-sitosterol, baicalin, eugenol, moslosooflavone, palmitic acid, oroxylin-A 7-O-glucuronide, and scutevulin as the potential active compounds responsible for the efficacy of HQ against both E. coli and S. aureus. The spectrum-effect relationship was utilized to reveal the orientation activities, with the results as follows: 1) The main basic-efficacy components in HQ with antibacterial, anti-inflammatory, and anticoagulant effects were P5, P8, P9, P15, P18, P19, P20; while the general basic-efficacy components were P2, P3, P6, P7, P11, P14, P21, P22, P28. 2) The main efficacy-oriented components in HQ with antibacterial effects on E. coli were P1, P12, P17, while the general efficacy-oriented compound was P10, P24, P25, P26, P27; the main efficacy-oriented in HQ with antibacterial effects on S. aureus were P14 and the general efficacy-oriented components were P1, P12, P26, P29, P30, respectively. 3) The main efficacy-oriented components with anti-inflammatory activity were P14, P24, P25, P27, and P30, while the general efficacy-oriented components were P13, P23, P26. 4) The main efficacy-oriented compounds in HQ with effects on anticoagulation were P6 and P22; these acted by prolonging APTT through the intrinsic coagulation pathway and PT through the extrinsic coagulation pathway, respectively. 5) The pharmacodynamic status classification of Scutellaria baicalensis ingredients were confirmed by nine reference compounds exemplarily. Conclusion: This work established a novel strategy for active compound efficacy status identification in multi-tropism Chinese herbal medicine (Scutellaria baicalensis Georgi) based on multi-indexes spectrum-effect gray correlation analysis, the method is scientific feasible and can be applied to the effective substances identification and quality control of other CHM. Graphical abstract: Image 1